Endometrial CD16(+) and CD16(-) NK cell count in fertility and unexplained infertility - Junovich, Gisela Yael (2013)
Problem: Peripheral counts of CD16+ NK cells have been well characterized in reproductive failure. However, not enough case-control clinical studies have been conducted to establish normal or abnormal CD16+/- values in the endometrium. Method of Study: Peripheral and endometrial NK cell counts by FACS, IL-6 and VEGF cytokines levels by ELISA were characterized in fertile women and unexplained infertility patients with implantation failures (UI-IF) during implantation window. ROC and correlation analysis were performed. Results: ROC analysis revealed endometrial CD16+ NK cells, IL-6 and VEGF as good diagnostic parameters for unexplained infertility. Almost half of UI-FI patients showed increased total and CD16+ NK cell counts correlating with decreased levels of endometrial IL-6 and VEGF. No correlation was found with peripheral blood values. Conclusions: Increased CD16+ NK cells were associated to IL-6 and VEGF deficiency in a high proportion of UI-IF patients. Testing for these immunomarkers could be a potential tool in infertility diagnosis.